1995
DOI: 10.1038/nm0595-460
|View full text |Cite
|
Sign up to set email alerts
|

A placental clock controlling the length of human pregnancy

Abstract: We report the existence of a 'placental clock', which is active from an early stage in human pregnancy and determines the length of gestation and the timing of parturition and delivery. Using a prospective, longitudinal cohort study of 485 pregnant women we have demonstrated that placental secretion of corticotropin-releasing hormone (CRH) is a marker of this process and that measurement of the maternal plasma CRH concentration as early as 16-20 weeks of gestation identifies groups of women who are destined to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
621
2
19

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 853 publications
(669 citation statements)
references
References 21 publications
27
621
2
19
Order By: Relevance
“…It is important to note that GCs, pro-inflammatory cytokines, anoxic conditions, and stress conditions of pregnancy (i.e., preeclampsia) stimulate the secretion of pCRH [115,119] . This correlates with the high circulating levels of CRH in women delivered preterm compared to the low levels in women delivered at or after term [119,120] .…”
Section: Placental Crhmentioning
confidence: 71%
See 1 more Smart Citation
“…It is important to note that GCs, pro-inflammatory cytokines, anoxic conditions, and stress conditions of pregnancy (i.e., preeclampsia) stimulate the secretion of pCRH [115,119] . This correlates with the high circulating levels of CRH in women delivered preterm compared to the low levels in women delivered at or after term [119,120] .…”
Section: Placental Crhmentioning
confidence: 71%
“…It is important to note that GCs, pro-inflammatory cytokines, anoxic conditions, and stress conditions of pregnancy (i.e., preeclampsia) stimulate the secretion of pCRH [115,119] . This correlates with the high circulating levels of CRH in women delivered preterm compared to the low levels in women delivered at or after term [119,120] .Recent studies have shown that pregnant women with depression display high levels of pCRH that may contribute to serious medical complications or outcomes in mother and baby [5] . pCRH has been shown to be a crucial peptide hormone in fetal development, and increased levels of this peptide in the fetal circulation correlate with altered distribution and expression of GC receptors in the fetal brain [5,74] .…”
mentioning
confidence: 99%
“…Placental corticotrophin releasing hormone (CRH) and fetal glucocorticoids are key regulators of the timing of delivery. 48 The length of gestation has been linked with maternal plasma CRH levels, 49 and stress-related pretermdelivery is thought to be mediated by changes in CRH and glucocorticoid secretion. 50,51 There is good evidence that prenatal glucocorticoid exposure alters not only the development of the HPAA but also sympathetic innervation 52 and cardiac noradrenergic and sympathetic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Women in preterm labour have significantly elevated levels of CRH compared to non-labouring women of the same gestation, a finding that can also be seen several weeks in advance of clinical signs of preterm labour (McLean et al, 1995, Wadhwa et al, 1998. Taken together, these observations form the hypothesis that CRH may function as a placental clock in humans, determining the length of gestation and onset of labour (McLean et al, 1995). A positive feedback loop has been proposed whereby fetal glucocorticoids, produced by the maturing fetal adrenal glands, promote placental CRH gene expression and CRH production, which in turn stimulates further fetal cortisol production via the HPA axis (Robinson et al, 1988).…”
Section: Corticotropin-releasing Hormone and The "Placental Clock"mentioning
confidence: 97%
“…CRH binding protein (CRH-BP) produced by the liver and placenta, limits the bioavailability of CRH but its levels fall during the last six weeks of pregnancy leaving increased levels of free CRH (Linton et al, 1993). Women in preterm labour have significantly elevated levels of CRH compared to non-labouring women of the same gestation, a finding that can also be seen several weeks in advance of clinical signs of preterm labour (McLean et al, 1995, Wadhwa et al, 1998. Taken together, these observations form the hypothesis that CRH may function as a placental clock in humans, determining the length of gestation and onset of labour (McLean et al, 1995).…”
Section: Corticotropin-releasing Hormone and The "Placental Clock"mentioning
confidence: 99%